Stress and academic achievement in students of dentistry - Evaristo-Chiyong, Teresa (2015)
The purpose of this study was to evaluate academic stress and its impact in the academic performance of students of dentistry. Methodology: we worked with a probabilistic sample of 186 dental students who completed the semester 2014-1, stratified by year of study: first (n = 37); second (n = 29); third (n = 44); fourth (n = 36) and fifth (n = 40) and single randomly selected. The measurement of academic stress variable was performed through the SISCO inventory validated questionnaire, which assesses: academic stressors, manifestations of stress and coping strategies and obtained an internal consistency of 0.768. The academic performance variable was measured by the average student at the end of the semester 2014-1. For statistical analysis, bivariate and multivariate statistical tests were used. Results and conclusions: it was found that 100% of the students presented sometime stressful situation with an average intensity of 3.5. The average academic performance was 13.21. Students in the senior years of study have a higher academic performance, demonstrating no statistically significant differences by sex. It was found in the multivariate analysis that assertive ability is the determining factor in academic performance of students of dentistry (Beta 0.167, p <0.05).